Dualistic Hessian Structures Among the Thermodynamic Potentials in the κ-Thermostatistics - Tatsuaki Wada; Hiroshi Matsuzoe; Antonio M. Scarfone (Entropy, 2015)
We explore the information geometric structures among the thermodynamic potentials in the κ-thermostatistics, which is a generalized thermostatistics based on the κ-deformed entropy. We show that there exists two different kinds of dualistic Hessian structures: one is associated with the κ-escort expectations and the other with the standard expectations. The associated κ-generalized metrics are derived and related to the κ-generalized fluctuation-response relations among the thermodynamic potentials in the κ-thermostatistics.